2013
DOI: 10.5142/jgr.2013.37.332
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of ginsenoside accumulation in Panax ginseng as a result of γ-irradiation

Abstract: In this study, gamma rays were used to irradiate embryogenic calli induced from cotyledon explants of Panax ginseng Meyer. After the embryogenic calli were irradiated, they were transferred to adventitious roots using an induction medium; next, mutated adventitious root (MAR) lines with a high frequency of adventitious root formations were selected. Two MAR lines (MAR 5-2 and MAR 5-9) from the calli treated with 50 Gy of gamma rays were cultured on an NH4NO3-free Murashige and Skoog medium with indole-3-butyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 38 publications
(38 reference statements)
1
18
1
Order By: Relevance
“…Moreover, heterologous expression of PgHMGR1 caused 1.8-to 2-fold increase in phytosterols, including β-sitosterol, campesterol, cycloartenol, and 2-to 2.5-fold increase in triterpenes, including α-amyrin and β-amyrin in transgenic Arabidopsis rosette leaves . Consistently, a similar result was achieved by Kim et al (2013a), and it was shown that the A. rhizogenes-mediated ectopic overexpression of PgHMGR1 caused 1.5-to 2.5-fold increase of triterpene and 1.1-to 1.6-fold higher phytosterols in Platycodon gradiflorum hairy root. These results again confirmed conserved role of PgHMGR1 in triterpene and phytosterol accumulation in plants.…”
Section: Transgenic Plantssupporting
confidence: 77%
“…Moreover, heterologous expression of PgHMGR1 caused 1.8-to 2-fold increase in phytosterols, including β-sitosterol, campesterol, cycloartenol, and 2-to 2.5-fold increase in triterpenes, including α-amyrin and β-amyrin in transgenic Arabidopsis rosette leaves . Consistently, a similar result was achieved by Kim et al (2013a), and it was shown that the A. rhizogenes-mediated ectopic overexpression of PgHMGR1 caused 1.5-to 2.5-fold increase of triterpene and 1.1-to 1.6-fold higher phytosterols in Platycodon gradiflorum hairy root. These results again confirmed conserved role of PgHMGR1 in triterpene and phytosterol accumulation in plants.…”
Section: Transgenic Plantssupporting
confidence: 77%
“…As the major physiological role of the ginsenosides is related to plant defense [198,199], stress-inducible factors have been used in order to improve their production. Treatments with methyl jasmonate and salicylic acid generally induced oxidative stress and increased ginsenoside content, as well as gamma-irradiation, which enhanced the final product up to 16-fold [200,201].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…This has made the generation of superior genotypes by conventional breeding difficult. Therefore, attempts have been made to achieve a more rapid and increased production of the ginsenosides using other methods such as classical tissue culture [6] , bioreactor culture [7] , Agrobacterium -mediated hairy root production [8,9] , using elicitors in cell cultures [10–12] , and mutation breeding by γ-irradiation [13,14] . The last method has been used in many other plant species and has provided a large number of variants useful for plant breeding [15–17] .…”
Section: Introductionmentioning
confidence: 99%
“…The last method has been used in many other plant species and has provided a large number of variants useful for plant breeding [15–17] . Mutagenesis by γ-irradiation has been shown to enhance ginsenoside production in P. ginseng [13,14] . Recently, we have also generated mutant cell lines by applying γ-irradiation on P. ginseng adventitious roots which were derived from Korean wild ginseng root [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation